Preferences for token exchange‐production schedules: Effects of task difficulty and token‐production schedules. (18th December 2019) - Falligant, John M.; Pence, Sacha T.; Bedell, Sarah B.
Abstract : Previous research suggests that accumulated exchange‐production schedules promote increased work completion and are more preferred than distributed exchange‐production schedules. The purpose of this study was to evaluate whether the response effort or token‐production schedules associated with token delivery influenced preferences for exchange‐production schedules. Tokens exchanged under accumulated schedules were more preferred, relative to distributed schedules, when tokens were earned for completing easy tasks. When participants earned tokens for completing difficult tasks, two of three participants preferred accumulated exchange‐production schedules (Experiment 1). Under dense token‐production schedules, accumulated exchange‐production schedules were preferred, but participant's preferences switched to distributed schedules under increasing token‐production (i.e., leaner) schedules (Experiment 2).